Evaluative conditioning affects the subsequent acquisition of differential fear conditioning as indexed by electrodermal responding and stimulus evaluations. (17th November 2019) - Lipp, Ottmar V.; Luck, Camilla C.; Muir, Alana C.
Abstract: It is currently unclear whether the acquisition of negative stimulus valence in evaluative and fear conditioning paradigms is interrelated or independent. The present study used a transfer paradigm to address this question. Three groups of participants were trained in a picture‐picture evaluative conditioning paradigm before completing acquisition of differential fear conditioning using graphical shapes as conditional stimuli (CSs). In group congruent, the shape used as CS+ (paired with the US during fear conditioning) was paired with negative pictures, whereas the shape used as CS− (presented alone during fear conditioning) was paired with positive pictures. In group incongruent, the shape used as CS+ was paired with positive pictures, whereas the shape used as CS− was paired with negative pictures. In group different, different shapes were employed in evaluative and fear conditioning. Acquisition of differential electrodermal responses emerged within fewer acquisition trials in groups congruent and different than in group incongruent. Transfer of evaluative learning across paradigms was evident only after removal of participants who failed to display evaluative conditioning. The current research indicates that stimulus valence acquired during evaluative conditioning transfers to fear conditioning and will differentially affect the acquisition of fear learning as indexed by subjective evaluations and electrodermal responses. The findings suggest that evaluative and fear conditioning are not independent. Abstract : The relationship between evaluative conditioning and fear conditioning is currently unclear. We show transfer of evaluative conditioning to subsequent fear conditioning not only for stimulus valence but also for the acquisition of differential electrodermal responses. This transfer of emotional learning across two very different learning paradigms suggests new approaches to preventing the acquisition or strengthening of the extinction of conditioned fear.